A perspective-based analysis of attachment from prenatal period to second year postnatal life - Santaguida, Erica; Bergamasco, Massimo (Frontiers in Psychology, 2024)
Attachment is one of the foundational themes in the history of the psychological development of human beings. For this reason, we assume that it must be approached by taking into account multiple scientific perspectives. The present review aims at analyzing the state of the art regarding the genetic, neurobiological and cognitive mechanisms underlying the development of attachment bonding, considering the child as the frame of reference. We hypothesize that attachment may be present in prototypical forms even in the prenatal period, thus our analysis has a temporal origin in the intrauterine period preceding birth. The intrauterine period is assumed to be a period of maximum sensitivity to stimuli and in particular to those coming from a potential primary caregiver: the biological mother. We conclude with a reframing of the state of the art and propose that future research work would benefit from a superordinate model of attachment, capable of containing and regulating all its components and variables.